Assessment of Citizenship Education Learning (PPKn) on Character Education Material at Elementary School Level - Wita Pratiwi (International Journal of Students Education, 2024)
Character education has an important role in the elementary school curriculum, especially in local content subjects, where apart from conveying material, it also functions as a reinforcement of values such as tolerance, religiosity, discipline, democracy, the spirit of nationalism and love of the homeland. The importance of developing character education based on Pancasila values is very real considering that school children are now very influenced by technological developments, which are often used for activities that do not support education, and even become tools for cyberbullying behavior and the formation of closed personalities. This research aims to conduct a literature review of PPKn learning on character education material in elementary schools, using the Systematic Literature Review (SLR) method. Data was collected by documenting and reviewing all articles related to Civics learning obtained via Google Scholar. The research results show that all learning models can be effectively used to achieve good learning outcomes for students, with video learning media being the most commonly used. It is hoped that by studying character education material in PPKn learning, students' abilities and knowledge about Pancasila values can be improved more optimally.